COVID-19 and the Okun’s law: the case of Ghana1 - Amaama Abdul Malik; Asad Ul Islam Khan (Cogent Economics & Finance)
The Covid 19 pandemic was a strong shock that plummeted into the entire interconnected economic activities of the world. As a result of the lockdown associated with the pandemic, the economies of the world were affected through restrictions like lockdown leading to the reduction of economic indicators like Gross Domestic Product (GDP) and increase in Unemployment. This paper set out to look at the relationship between the GDP and unemployment in Ghana in the periods prior and during the covid pandemic. The Autoregressive Distributed Lag (ARDL) model was used on data from 1991 to 2021. The result shows the nonexistence of the Okun’s law in Ghana in each of these periods. We conclude by advising policy makers to implement policies that directly generate more jobs like improvement in the agriculture sector through training and financial support to enable increased employment to match the increase in economic growth.